Morphological and molecular characterisation of a new awl nematode, Dolichodorus mediterraneus sp. n. (Nematoda: Dolichodoridae), from Spain (Nematology, 2007)
A new species of awl nematode, Dolichodorus mediterraneus sp. n., is described from southern Spain. The new species is described and illustrated by light microscopy and scanning electron microscopy studies from specimens collected in a sandy soil around roots of cork oak (Quercus suber L.) from Hato Raton, Aznalcázar (Seville), southern Spain. Dolichodorus mediterraneus sp. n. is characterised by a prominent, rounded, lip region, which is offset from the body and has four to six very fine annuli; lateral fields areolated with three lines, ending posterior to anus level; tail 72-122 μm long, abruptly tapering to an acuminate, often spicate, terminus; tail projection 51-79 μ m long; spicules ventrally arcuate, 33-42 μm long; gubernaculum slightly ventrally curved, 14-22 μm long. Scanning electron microscopy observations showed a similar en face pattern to other Dolichodorus spp. Molecular data from the ribosomal large subunit D2-D3 expansion segment of 28S rDNA from paratypes yielded a single fragment of approximately 800 bp. This is the first record of the genus Dolichodorus in Spain and only the second in Europe. A key to species is provided.